2022
DOI: 10.1111/jce.15349
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed‐field ablation combined with ultrahigh‐density mapping in patients undergoing catheter ablation for atrial fibrillation: Practical and electrophysiological considerations

Abstract: Background: Pulsed-field ablation (PFA) yields a novel ablation technology for atrial fibrillation (AF). PFA lesions promise to be highly durable, however clinical data on lesion characteristics are still limited.Objective: This study sought to investigate PFA lesion creation with ultrahighdensity (UHDx) mapping.Methods: Consecutive AF patients underwent PFA-based pulmonary vein isolation (PVI) using a multispline catheter (Farwave, Farapulse Inc.). Additional ablation, including left atrial posterior wall iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 27 publications
5
63
1
Order By: Relevance
“…Nevertheless, the limited published data on LAPWI so far demonstrate high acute and chronic LAPW isolation rates. 10,11 In our cohort, no esophageal lesion was detected. Also, in the Manifest-PF survey no esophageal lesion was found in a large patient cohort of 1758 patients undergoing PFA including LAPWI in a minor portion of patients.…”
Section: Left Atrial Posterior Wall Isolationmentioning
confidence: 50%
“…Nevertheless, the limited published data on LAPWI so far demonstrate high acute and chronic LAPW isolation rates. 10,11 In our cohort, no esophageal lesion was detected. Also, in the Manifest-PF survey no esophageal lesion was found in a large patient cohort of 1758 patients undergoing PFA including LAPWI in a minor portion of patients.…”
Section: Left Atrial Posterior Wall Isolationmentioning
confidence: 50%
“…In a pre-market trial, the same PFA device that was used in our study was successful in LAPW isolation in 25/25 patients (13,14) . With a different PFA catheter platform allowing for focal lesions, application of a roof line using PFA was effective in 22/22 patients (23).…”
Section: Roof Line and Left Atrial Posterior Wall Isolationmentioning
confidence: 67%
“…Gunawardene et al reported successful mitral isthmus ablation using PFA in two patients without the need for additional RFA. However, in one case, coronary artery spasm occurred after eight PFA applications and resolved upon administration of nitroglycerin (13). Although coronary arteries did not display particular susceptibility to PFA in animal models (22) or in our own clinical experience in any patients, the risk of coronary artery spasm during ablation of the mitral isthmus area needs further investigation.…”
Section: Standard Mitral Isthmus Linementioning
confidence: 85%
See 1 more Smart Citation
“…However, this catheter is only approved for catheter ablation of AF by means of pulmonary vein isolation. Therefore, data on the use of PFA applied to substrates other than the pulmonary veins are limited (2,3).…”
mentioning
confidence: 99%